Investigating arsenic toxicity in tropical soils: A cell cycle and DNA fragmentation approach - Alvarenga, Ingrid Fernanda Santana; dos Santos, Fabio Eduardo; Silveira, Graciele Lurdes; Andrade-Vieira, Larissa Fonseca; Martins, Gabriel Caixeta; Guilherme, Luiz Roberto Guimarães (The Science of the total environment, 2020)
Arsenic (As) is a metalloid and a toxicant that is found naturally in many environmental compartments, soils included. Soils with high levels of As occur worldwide and might pose a threat not only to humans, but also to many ecosystems. Considering the scarcity of studies regarding cytogenotoxic effects of model plants in As-contaminated soil, mainly in tropical areas, this study proposes the use of Allium cepa root tip bioassays for a fast-track assessment of As toxicity in tropical soils. For this end, root tip cells of A. cepa were exposed to an Oxisol, an Inceptisol and a Tropical Artificial Soil (TAS) contaminated with increasing doses of As (0, 8, 14.5, 26, 46.5, 84, 150, and 270 mg kg−1). The effects of As on cell cycle, micronucleus formation, and DNA fragmentation were evaluated. In general, root tip cells exposure to As increases the frequency of chromosome abnormalities and micronucleus, in turn, decreasing the frequency of mitotic index. As-treated cells also presented an increase in the percentage of DNA damage observed in comet assay. Overall, the effects of As in TAS were more pronounced, than in the Oxisol, being the Inceptisol the less toxic. A discussion of each As effect in cells and the link with the soil type is presented and reveals that clastogenic effects of As in A. cepa cells seemed to be the mode of action of this soil contaminant. [Display omitted] •Exposure to As increased the frequency of DNA alteration and fragmentation in A. cepa.•Clastogenic effects caused by As were evident in Allium cepa root tip cells.•The comet assay showed that arsenic generates cell damage.